Literature Study on Types of Electronically Based Science Learning Media in Improving Students’ Science Literacy Skills - Syamsurizal Syamsurizal; Ayu Kartika; Lufri Lufri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
Science literacy is knowledge of the subject matter, the ability to ask and answer questions, acquire new information, describe scientific phenomena, and draw conclusions from data. The creation of computer-based learning materials is one of the many initiatives that have been taken to improve students’ science litteracy, and is absolutely necessary to continue this work.This study aims to review various literatures on the types of electronic-based science learning media in improving students' science literacy. This research is a literature study using 18 articles from 2018 to 2022 which come from accredited and non-accredited national articles. A total of 18 relevant research papers were analyzed and evaluated with respect to objectives and media. The purpose of these 18 research articles is to develop learning media in improving students' science literacy, increasing motivation, knowing the feasibility of learning media and knowing student responses to the media developed with types of learning media such as e-modules, e-books, e-LKPD, media with interactive multimedia, audio visual and web-based such as software.